Using Low-Cost Sensors and Citizen Science: Assessing Thermal Inequality in African Slums - S. A. Sampson; A. Abascal; J. Wang; S. Vanhuysse; I. Rodríguez Carreño; I. Garcia Ruiz; M. Kuffer (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Urban heat exposure is intensifying due to climate change and urbanisation, with disproportionate impacts on vulnerable populations. Unfortunately, many urban areas, particularly informal settlements, lack sufficient data for detailed analysis to understand these impacts. Traditional air temperature measurement methods—such as meteorological stations—are sparsely distributed in African cities, typically located on city outskirts (e.g., airports), and fail to capture localized temperature variations. This study explores the use of low-cost sensors and citizen science initiatives to measure air temperature with higher spatial resolution in informal and surrounding formal settlements. A two-stage process is employed to evaluate data quality: first, statistically assessing biases in low-cost sensor (LCS) measurements, and second, employing Monte Carlo simulations to quantify uncertainties. The resulting data reveals significant temperature differences between informal settlements and surrounding formal areas, with informal settlements consistently exhibiting higher temperatures. This approach not only highlights the value of low-cost sensors and citizen science in generating high-resolution temperature data but also provides insights into thermal inequalities between different urban environments.